Localisation of the UNSCR 1325 Agenda: Lessons from Post-Maidan Ukraine (2014–2020) - Dudko, Yeliena; Langenhuizen, Yvette (Journal of Regional Security, 2022)
Ukraine adopted its first National Action Plan (NAP) on UNSCR 1325 on Women, Peace and Security whilst facing an active military conflict on its territory. e country also invested in localising the Women, Peace and Security agenda through the development of regional and local action plans. Additionally, several ministries adopted sectoral action plans. is article looks at the context in which Ukraine developed its first NAP 1325 (post-Maidan) and assesses the NAP against global high-impact NAP indicators. The authors then focus on connections between the national and regional/local-level plans and conclude that Ukraine’s first NAP did ‘trigger’ localisation initiatives in the form of Regional Action Plans (RAP) on UNSCR 1325, with Local Action Plans having been initiated via a separate track. A certain level of synergy was realised between initiatives stemming from these plans. e authors do, however, conclude untapped potential remains to further nurture, facilitate and support bottom-up Women, Peace and Security initiatives in Ukraine.